2014
DOI: 10.3174/ajnr.a3880
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the T2 Relaxation Time of the Temporomandibular Joint Articular Disk between Patients with Temporomandibular Disorders and Asymptomatic Volunteers

Abstract: BACKGROUND AND PURPOSE: T2 relaxation time is a quantitative MR imaging parameter used to detect degenerated cartilage in the knee and lumbar intervertebral disks. We measured the T2 relaxation time of the articular disk of the temporomandibular joint in patients with temporomandibular disorders and asymptomatic volunteers to demonstrate an association between T2 relaxation time and temporomandibular disorder MR imaging findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
(26 reference statements)
2
9
0
Order By: Relevance
“…T2 values of the articular disc were reported in previous studies showing both similar (26.9 ± 3.7, 29.3 ± 3.8, and 25.19 ± 1.15 ms) 10 – 12 and much longer values (40.21 ± 2.95 ms) 13 in healthy volunteers compared to our TMD-negative volunteers. In those studies, MRI examinations were performed using TMJ surface coils.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…T2 values of the articular disc were reported in previous studies showing both similar (26.9 ± 3.7, 29.3 ± 3.8, and 25.19 ± 1.15 ms) 10 – 12 and much longer values (40.21 ± 2.95 ms) 13 in healthy volunteers compared to our TMD-negative volunteers. In those studies, MRI examinations were performed using TMJ surface coils.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have revealed a significantly longer T2 relaxation time in retrodiscal tissue 9 , but no significant differences in the articular disc 10 between volunteers and patients using a 1.5 Tesla (T) MR machine. Moreover, a study predicting intra- and inter-observer reproducibility of T2 mapping in asymptomatic volunteers at 3.0 T was also conducted and proven feasible for TMJ examination 11 .…”
Section: Introductionmentioning
confidence: 97%
“…Cao and Kakimoto performed T2 mapping of the articular disc demonstrating significant variations among the different portions of the disc [5] and prolongation of the T2 relaxation times of the disc with progressive degeneration [45]. Few studies have evaluated the application of UTE techniques in the TMJ [13,14,31].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Cao et al 68 and Schmid‐Schwap et al 69 found regional variation of T 2 values in different bands and layers of the TMJ disc, probably due to different orientations of collagen fibers in different histologic zones. Additionally, Kakimoto et al reported that the T 2 values of the TMJ disc were longer in patients with progressive TMD and older age groups compared to those of healthy volunteers and younger age groups, which they speculated might be attributed to the loss of collagen and proteoglycan in degenerating cartilages 72 . On the contrary, Bristela et al suggested that T 2 mapping did not seem to be a suitable diagnostic tool for TMJ imaging at present, because they found significant moderation effects between T 2 values of disc and other pathological conditions, especially joint effusion 63 .…”
Section: T2 Mappingmentioning
confidence: 99%